On the Mechanism of Particle Motion in Space and Time - Z., Omboo (Scientific transaction of the National University of Mongolia. Physics, 2022)
On the basis of a hypothesis about spiral motion of particles in space and time, It is derived from the theoretical expression for Planck constant and the De Broglie wave formulas and suggested a new physical constant.